DISINVASIVE EFFICACY OF THE DOMESTIC DRUG DEZSAN AGAINST EGGS OF NEMATODES OF THE GENUS TRICHURIS ISOLATED FROM SHEEP - Melnychuk, V.; Yevstafieva, V.; Yuskiv, I.; Zhulinska, O. (Scientific Progress & Innovations, 2022)
The paper presents the results of experimental studies to determine the disinvasive effica cy of the chemical chlorine-containing agent of domestic production Dezsan RPF «Brovapharma» (Ukraine). The research was carried out on the basis of the Laboratory of Parasitology of the Department of Parasitology and Veterinary and Sanitary Examination of Poltava State Agrarian University. Non-invasive and invasive test cultures of eggs of nematodes of the genus Trichuris of pathogens of sheep trichurosis (Trichuris ovis, T. skrjabini and T. globulosa) were used in the experiments. Tests of Dezsan on helminth eggs were performed at concentrations of 0.5, 1.0, 1.5 and 2.0 % at exposures of 10, 30 and 60 minutes. Studies have shown that the studied disinfectant has disinvasive properties against non-invasive and invasive test culture of nematode eggs of Trichuris ovis, T. skrjabini and T. globulosa. The unequal resistance of eggs of trichuris of different species to the action of the test agent in experiments in vitro has been proved. Dezsan showed a high level of disinvasive efficiency in relation to non-invasive and invasive test cultures of eggs: T. ovis in 1.0‒2.0 % concentrations at exposures of 10–60 min (DE – 92.94–100.00 %) and 1.0 and 1.5‒2.0 % concentrations at exposures of 30, 60 min and 10‒60 min, respectively (DE – 90.63–100.00 %); for test cultures of T. skrjabini eggs in 0.5 and 1.0‒2.0 % concentrations at exposures of 60 min and 10‒60 min, respectively (DE – 91.03–97.44 %) and 1.0‒2.0 % concentrations for all exposures (DE – 91.01–100.00 %); for test cultures of T. globulosa eggs in 0.5 % and 1.0‒2.0 % concentrations at exposures of 30 and 10‒60 min, respectively (DE – 91.30–100.00 %) and 1.0 % and 1.5‒2.0 % concentrations at exposures of 30–60 min, and 10–60 min (DE – 90.91–100.00 %). It was found that the domestic product Dezsan had a detrimental effect on the eggs of trichurises and led to their death due to the destructive action of the components of the drug on the shell, the embryo of parasites, the caps of eggs of trichurises. The data obtained by us allow us to recommend Dezsan as a disinfectant for the control and prevention of trichurosis in sheep farms, regardless of the type of helminths that parasitize animals.